The in situ formation of defective CoOOH catalysts from semi-oxidized Co for alkaline oxygen evolution reaction. Issue 37 (21st July 2022) - Wang, Lan; Pan, Ya; Wu, Dan; Liu, Xiaokang; Cao, Linlin; Zhang, Wei; Chen, Honglei; Liu, Tong; Liu, Dong; Chen, Tao; Ding, Tao; Wang, Yi; et al.
Abstract : Semi-oxidized Co pre-catalysts are oxidized and self-assembled into defective CoOOH with a much higher O vacancy density during the OER, benefiting the bonding of oxygen species on the catalyst surface and promoting the catalytic activity. Abstract : Electrochemical water splitting based on Co oxide electrocatalysts provides a promising means for renewable hydrogen production from water. Identifying the structure evolution and real-time active structure of Co-based electrocatalysts under operational conditions is crucial for understanding the OER mechanism and rational design of efficient catalysts. Here, we systematically synthesized three types of Co-based precatalysts, including Co/graphene oxide (GO), Co–CoO/GO and Co3 O4 /GO, to clarify the critical effects of the precatalyst structure for OER. The electrochemical test results confirm that the Co–CoO/GO precatalyst shows a lower overpotential compared to Co/GO and Co3 O4 /GO precatalysts and commercial RuO2 /C. A thorough in situ analysis by XAFS revealed that the Co–CoO/GO precatalysts are oxidized and self-assembled into CoOOH during water oxidation and possess a much higher O vacancy density compared with the CoOOH derived from Co/GO, while the Co3 O4 /GO precatalyst maintains its structure during operation. This strategy of in situ creation of defects in CoOOH provides a guideline for the rational design of future catalysis systems.